Community research in a public place: Wangangarra 1 rockshelter, Mitchell River National Park, East Gippsland (Australia). Issue 2 (3rd May 2020) - Roberts, Georgia L.; Mullett, Russell; David, Bruno; Fresløv, Joanna; ,; Mialanes, Jerome; Petchey, Fiona; McDowell, Matthew; Wong, Vanessa N. L.; Szabó, Katherine; Stoessel, Daniel; Krusic-Golub, Kyne; et al.
Abstract: Southeastern Australia' s temperate East Gippsland region is a large and diverse landscape that spans from the Bass Strait coast to the Australian Alps. The region includes a number of national parks and reserves jointly managed by Aboriginal Traditional Owners, the Gunaikurnai Land and Waters Aboriginal Corporation (the ' Gunaikurnai Corporation' ), and Parks Victoria. The Gunaikurnai Corporation recognises that archaeological research can be a fundamental tool in understanding relationships in past landscapes and managing places within Country. In 2017, the Gunaikurnai Corporation initiated a long-term collaborative study of Gunaikurnai Country with university-based scientists, with the management of Country through informed decision-making in mind. Here we present results from the first partnership research project in the Mitchell River National Park. A small-scale archaeological excavation of Wangangarra 1, a rockshelter that was not previously recognised to hold archaeological evidence, has revealed highly significant deposits spanning from before the Last Glacial Maximum to recent times, including evidence of occupation by the Old People. The results contribute to a better understanding of the Park as a cultural landscape, and demonstrate the success of respectful partnership research with local Indigenous groups as Traditional Owners.